Religion and education in the ancient Greek world - Salvo, Irene; Scheer, Tanja Susanne (SERAPHIM, 2021)
Cover -- Title -- Acknowledgements -- Table of Contents -- Abbreviations -- I. Introductions -- Irene Salvo/Tanja S. Scheer - Greek Religion and Education: Key Concepts and Aims -- Josine Blok - Educating Citizens: Knowledge, Competence, and Values in Greek Poleis -- II. Actors and Models -- Irene Salvo - The Pedagogical Function of Cult Associations in Late Classical Athens -- Eftychia Stavrianopoulou - Female Role Models in the Hellenistic Period: The Evidence of Religious Norms -- Marietta Horster - Sacred Personnel as Role Models in the Post-classical Period -- III. Performing Knowledge -- Susanne Gödde - Learning by Suffering? 'Education' and 'Religion' in Ancient Greek Theatre -- Sophie Marianne Bocksberger - Dancing Little Bears -- IV. Skills and Media -- Tanja S. Scheer - Conveying Religious Knowledge in Classical Athens: Imagery in Athenian Religious Discourse -- Aleksander Wolicki - Greek Priestesses and Literacy -- Serafina Cuomo - Numeracy in the Sanctuary -- V. Astrology, Philosophy, and Religion -- Ilaria Bultrighini - Theōn Hemerai: Astrology, the Planetary Week, and the Cult of the Seven Planets in the Graeco-Roman World -- Ilinca Tanaseanu-Döbler - Statues as Theological Treatises: Porphyry's Approach in Peri agalmaton in Context -- Contributors -- Index of personal names, gods, festivals, places, and key Greek terms.